Prática docente e tecnologias digitais na pandemia da Covid-19: uma etnopesquisa - Araújo, Silmara Cavalcante Oliveira de (2024)
In Brazil, the use of Digital Information and Communication Technologies (DICT) as educational resources has intensified due to the covid-19 pandemic, following the implementation of Emergency Remote Teaching (ERT). In this way, it became possible to continue teaching and learning during social distancing. However, discussions about the issues surrounding this topic have also increased, such as the lack or precarious access to digital media and the Internet, the unpreparedness of teachers and schools for the educational use of these resources, among others. Therefore, the object of study of this dissertation is the teaching relationship with DICT in education following the covid-19 pandemic and the ERT. As a research problem, I investigate the implications of using DICT in teaching practice and, consequently, in teacher training. The general objective of the research is to build an autobiographical and imagery narrative based on my training and professional experiences with the subject, between 2020 and 2022. As specific objectives, we have: a) analyze teaching practice with ERT and through DICT; b) discuss the social and school experience and the use of media during the covid-19 pandemic; and c) reflect on the implications of the gaps in teacher training regarding practices with DICT. The justification for writing this research came from my experience with ERT throughout 2020 and with blended learning in 2021, when concerns arose regarding a professional requirement that was more technical than teaching, since private educational institutions demanded from teachers a mastery of DICT as educational resources. Furthermore, there is a strong demand for the use of digital technologies in education in the Brazilian laws, such as the National Common Curricular Base (BNCC), which states the importance of immersion in digital culture for students, aiming for critical training for the use of these resources, as well as the relevance of teaching work with DICT. As a research methodology, I use a qualitative approach and work with the ethnography research method, since I classify it as a descriptive research according to its objectives. As for the research procedures, it was constructed an autobiographical narrative and an imagetic narrative. Regarding the theoretical foundation, I dialogue with the concepts of practice and teacher training by Antonio Nóvoa, media education by Bévort and Belloni and Mônica Fantin, social and school experience by Dubet, convergence culture by Henry Jenkins and cultural mediation by Jesús Martín-Barbero and Guillermo Orozco. Finally, the research demonstrated that it is necessary to update teacher training regarding the use of DICT in education, in addition to a more attentive and critical look at the digital exclusion faced by a large part of Brazilian students, since, throughout remote teaching, these were some of the main challenges reported by teachers during the covid-19 pandemic.